Biomechanical Evaluation of Neuro-occlusal Rehabilitation for Occlusal Imbalance Correction in Children with Facial Asymmetry - Ortún-Terrazas, Javier; Cegoñino, Jose; Santana-Penín, Urbano; Illipronti-Filho, Edson; Pérez del Palomar, Amaya (Jornada de Jóvenes Investigadores del I3A, 2018)
Contemporary eating habits may cause malformations in children jaw, that are difficult to evaluate and treat clinically. In this work, a computational methodology for the diagnosis and the treatment of this pathology is proposed. It combines porous-fibrous material models, medical devices and computational models of patients with facial asymmetries from the perspective of neuro-occlusal rehabilitation.